Exosomes Derived From Mesenchymal Stem Cells Ameliorate Renal Ischemic-Reperfusion Injury Through Inhibiting Inflammation and Cell Apoptosis - Li, Long; Wang, Rulin; Jia, Yichen; Rong, Ruiming; Xu, Ming; Zhu, Tongyu (Frontiers in Medicine, 2019)
The renoprotection of mesenchymal stem cells (MSC) following kidney ischemia reperfusion injury (IRI) have been reported recently, thus the present study aimed to investigate the protective mechanism of MSCs in a rat IRI model. Rats were divided into five groups according to the different treatments: sham group, IRI group, MSC group, MSC-ex group and MSC-ex+RNAase group, and kidney function, pathological conditions, proinflammatory cytokines, transcription factors and cell apoptosis were assessed. The results revealed that MSCs and exosomes from MSCs reduced the levels of Scr and BUN, suggesting a renoprotective effect in IRI. In addition, the expression of pNF-κB and pIκB was decreased in the MSC and MSC-ex groups, but total IκB expression was increased. As for apoptosis, MSC and exosomes both reduced the expression of caspase-9, cleaved caspase-3 and Bax, and increased the levels of Bcl-2, confirming the anti-apoptotic function in a rat renal IRI model. However, based on our findings, the MSC-ex+RNAase group shared the same features as the IRI group, likely due to the ability of RNA hydrolase to eliminate the function of exosomes. Mechanistically, exosomes originating from MSCs have protective functions in IRI via downregulation of the level of apoptotic and inflammatory response, in which the NF-κB signaling pathway plays a key role, suggesting a new mechanism for the renal protection of MSCs.